Metode Penguatan Pendidikan Karakter Peserta Didik Sekolah Dasar (Studi Kasus Di SDIT Bias Assalam Kota Tegal) - Kurotul Aeni (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Various deviations that occur in society today, related to character values ​​and moral decline among young people are of concern. This situation is exacerbated by the morale of leaders and law enforcers who are far from the value of the character of Pancasila as the nation's philosophy. The national education system is considered to be the most responsible for the emergence of these problems in order to build and fortify the character of students. Character education requires the right method so that there is strengthening in its implementation, so that efforts to shape the character of students are achieved. This qualitative research with the naturalistic inquiry approach aims to describe and analyze methods of strengthening character education and its achievements at SDIT BIAS Assalam, Tegal city. Collecting data using observation, interviews, and documentation. The validity of the data was carried out by confirming the results of observations, interviews, documents. The data credibility test is done by extending observations, increasing persistence, data triangulation, negative case analysis, member checks, and references. Data analysis used the interactive model of Miles & Huberman. The results showed that the method of strengthening character education used in SDIT BIAS Assalam included the continuous character building method so that the students' habits were integrated in every school activity, both intracurricular, co-curricular, and extracurricular. In addition to being integrated with other activities, the role of adults in giving examples also influences character, other factors involving the school community in providing and implementing commitment to school norms and traditions (providing motivation, advice, understanding and appreciation of affective messages) have a good impact on goals. character education at SDIT BIAS so that it can be carried out and can take place as expected.